High-density metallic nanogaps fabricated on solid substrates used for surface enhanced Raman scattering - Lu, Gang (2013)
The Raman signal of adsorbed molecules can be significantly enhanced by utilizing metallic structures with high-density Raman hot spots used as surface enhanced Raman scattering (SERS) substrates. In this work, we develop a simple, convenient and tunable method to fabricate high-density Ag or Au nanogaps on Si wafers. These nanogaps can serve as Raman hot spots, leading to dramatic enhancement of the Raman signal. The high-density nanogaps can be formed by repeating the electroless deposition of Ag NPs (or Au NPs) and coating of p-aminothiophenol (PATP, a Raman probe) on the deposited Ag NPs (or Au NPs) through the self-assembly process. After removal of PATP by O2 plasma, the as-fabricated SERS substrate can be reused for the detection of other molecules.